Evaluation of story response in seismic prone building construction using high damping rubber bearing - SaifulIslam,A.B.M. (Revista de la Construcción. Journal of Construction, 2018)
Significantly growing construction in the earthquake vulnerable regions needs appropriate handling of seismic prone buildings. Insertion of high damping rubber bearing (HDRB) at the building base might be an attractive option for structural safety and economy. This study deals with incorporation of HDRB device in building base and focus on the change of structural behavior for its different categories. Structural responses of base isolated (BI) buildings under site- specific seismic excitation are analyzed. The superstructure of multistoried buildings is represented by a finite element (FE) model comprising multi-degree of freedom. The structural analyses involve the BI as well as fixed base (FB) buildings. The commercial finite element packages SAP 2000 has been used to determine the variation in structural responses performing static and dynamic analyses. Twenty prototype building frames are modelled considering four HDRB categories. The HDRB is found to make the buildings more flexible reducing the seismic responses. The increased natural period leads more importance of building flexibility effects and so the horizontal shift of superstructure increases. The story shear reduces significantly and eventually the reduced overturning moment indicates that the forces are highly overestimated if the bearing is not employed. The acceleration profile presents good agreement with the isolation strategy. Without bearing, story accelerations will be largely glorified. To lessen corresponding story shears and story accelerations HDRB can be chosen as per the specifications and necessities. Such HDRB isolated buildings can withstand rather high seismic tremors in a safe and efficient manner due to radical reduction of story responses and good structural flexibility.